Occurrence and distribution of marsh clam,polymesoda spp. in Marudu Bay, Sabah,Malaysia - Julian Ransangan; Tan Kar Soon (Scientific Research Publishing, 2018)
Marudu Bay is part of the Tun Mustapha Marine Park, the largest marine protected area within the Malaysian region of the Coral Triangle Initiative. The bay is known for its diversed fisheries resources including bivalves. Although some of these bivalve species are commercially important, their occurrence, distribution and stock status in the bay are not well documented. Hence, the current study was conducted to determine the occurrence, distribution and the stock status of marsh clam, Polymerasoda spp. in the mangrove swamp situated at the southernmost of the Marudu Bay. Samplings were carried out at the mangrove swamps which covered an area of 500 sequare meter per sampling site. Two marsh clams species, Polymesoda erosa and P. expansa were found to inhabit the sampling sites. In general, juvenile marsh clams were noticed to dominate the seaward mangrove swamp, whereas the high tidal regions were dominated by adults. The current study also suggested a link in the distribution and the morphometric measurements of the marsh clams with the sediment grain size.